Emerging role of RNF2 in cancer: From bench to bedside - Yan, Qi; Chen, Bang‐jie; Hu, Shuang; Qi, Shun‐li; Li, Liang‐yun; Yang, Jun‐fa; Zhou, Hong; Yang, Chen‐chen; Chen, Li‐jian; Du, Jian (Journal of cellular physiology, 2021)
RNF2 (also known as ding, Ring1B or Ring2) is a member of the Ring finger protein family, which functions as E3 ubiquitin ligase for monoubiquitination of histone H2A at lysine 119 (H2AK119ub). RNF2 gene is located at the 1q25.3 site of human chromosome and the coding region is composed of 9 exons, encoding 336 amino acids in total. Many studies have demonstrated that overexpressed RNF2 was involved in the pathological progression of multiple cancers and has an impact on their clinical features. For instance, the upregulated expression level of RNF2 is positively correlated with the occurrence and progression of hepatocellular carcinoma, melanoma, prostate cancer, breast cancer, pancreatic cancer, gastric cancer, and bladder urothelial carcinoma, as well as with the radioresistance of lung cancer and chemoresistance of ovarian cancer. This review provides an up‐to‐date perspective on the relationship between RNF2 and several cancers and highlights recent studies on RNF2 regulation. In particular, the relevant cellular signaling pathways and potential clinical value of RNF2 in cancers are also discussed, suggesting its potential as an epigenetic biomarker and therapeutic target for these cancers. (1). Elevated expression of RNF2 is closely related to the occurrence and progression of cancer. (2). RNF2 is involved in a variety of cellular signaling pathways associated with cancer occurrence and progression. (3). RNF2 may serve as a potential diagnostic and prognostic marker and therapeutic target.